2013
DOI: 10.1007/s00425-013-1862-8
|View full text |Cite
|
Sign up to set email alerts
|

Homologous expression of cytosolic dehydroascorbate reductase increases grain yield and biomass under paddy field conditions in transgenic rice (Oryza sativa L. japonica)

Abstract: Dehydroascorbate reductase (DHAR, EC 1.8.5.1) maintains redox pools of ascorbate (AsA) by recycling oxidized AsA to reduced AsA. To investigate whether DHAR affects rice yield under normal environmental conditions, cDNA-encoding DHAR (OsDHAR1) was isolated from rice and used to develop OsDHAR1-overexpressing transgenic rice plants, under the regulation of a maize ubiquitin promoter. Incorporation and expression of the transgene in transgenic rice plants was confirmed by genomic polymerase chain reaction (PCR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…According to previous studies, the expression of OsDHARs in rice leaves could effectively assist the other antioxidant enzymes that are involved in the AsA-GSH cycle in reducing the effects of oxidative stress (Noctor and Foyer, 1998). The upregulated DHAR transcripts were detected for some plants and tissues exposed to short-term abiotic stresses (Kim et al, 2013). In this study, two OsDHARs (OsDHAR1 and OsDHAR2) showed genotypic changes in their transcript levels and temporal patterns, in that, the two OsDHARs showed consistently repressed expressions for the esl rice leaves during the whole sampling period (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to previous studies, the expression of OsDHARs in rice leaves could effectively assist the other antioxidant enzymes that are involved in the AsA-GSH cycle in reducing the effects of oxidative stress (Noctor and Foyer, 1998). The upregulated DHAR transcripts were detected for some plants and tissues exposed to short-term abiotic stresses (Kim et al, 2013). In this study, two OsDHARs (OsDHAR1 and OsDHAR2) showed genotypic changes in their transcript levels and temporal patterns, in that, the two OsDHARs showed consistently repressed expressions for the esl rice leaves during the whole sampling period (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…For OsMDHAR, this small gene family comprises five isoform members: two cytosolic isoforms (OsMDHAR1 and Os MDHAR2), two membrane-bound peroxisomal isoforms (OsMDHAR3 and OsMDHAR4), and one chloroplastic isoform (OsMD-HAR5) (Teixeira et al, 2005). DHAR enzymes are encoded by two isoform genes (OsDHAR1, and OsDHAR2) (Kim et al, 2013). However, to date, information on the transcriptional profile and temporal patterns of these isoform expressions during rice leaf senescence is lacking, and the interaction between the transcript expression of distinct OsAPX isoform genes and H 2 O 2 accumulation in the initiation and progression of the senescing leaves remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…During this study, we examined the effect of AtCBF3 gene with respect to ascorbic acid contents; which is an antioxidant enzyme and creates chilling tolerance in tomato transgenic lines (Kim et al, 2013). Under normal temperature (25 ºC), AtCBF3 plants and WT plants did not exhibit any distinguishable differences in AsA contents.…”
Section: Atcbf3 Improves Ascorbic Acid Contentsmentioning
confidence: 99%
“…Plants hold antioxidant enzymes that have been best characterized for their protective roles in photosynthetic machinery by scavenging toxic free radicals and also act as signaling molecules to regulate the expression of cold defense genes (Gill et al, 2013). Ascorbic acid (AsA) is an essential antioxidant that detoxifies ROS generated during cold stress, and it also acts as a co-factor for many enzymes (Kim et al, 2013). AsA has been reported to regulate cell division and growth by acting as a signal transduction molecule (Green and Fry, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, detailed information about AsA biosynthesis in rice is missing. The homologous overexpression of the recycling enzyme dehydroascorbate reductase (DHAR) in rice lead to enhanced foliar AsA redox state and improved grain yield and biomass under field conditions (Kim et al 2013). Together, these investigations suggest that the understanding of AsA biosynthesis in rice has important implications in the breeding for biomass and stress related traits of the world's most important food crop.…”
Section: Introductionmentioning
confidence: 99%